Estrategias metodológicas activas para elevar la motivación en el área de matemáticas en los estudiantes de 4to año de EGB de la escuela Víctor Manuel Villamarin Gómez - Rivadeneira Villao, Odalis Karlibeth (2023)
The use of active methodological strategies in teaching the mathematical area is of great importance to motivate students and ensure that they possess skills and abilities during their educational process. The main objective of the case study was to identify active methodological strategies that help raise motivation in the area of mathematics in 4th year EGB students at the Víctor Manuel Villamarín Gómez School. The strategies that were provided in the inquiry are mainly the inverted classroom process and project-based learning which make the student participatory and the teacher is a guide to the work that the student does individually or in groups. In summary, the implementation of active methodological strategies in teaching the area of mathematics allows students to be involved in a significant, dynamic, participatory way. This is only achieved with the correct use of these strategies with the aim of increasing motivation for this specific area of learning. In the research process, information with bibliographic content was obtained, techniques and instruments were used that are detailed in the current case study.